2018
DOI: 10.1075/lab.17004.rad
|View full text |Cite
|
Sign up to set email alerts
|

The perception and interpretation of sentence types by L1 Spanish–L2 English speakers

Abstract: While the L2 perception of segmentals has been investigated, our knowledge of the L2 perception of intonation is limited. Moreover, it is unclear how context affects L1 transfer. This study investigates the perception of English sentence types by adult L1 Spanish speakers across tasks varying in contextual information. In Task 1, participants heard low-pass filtered utterances and identified them as statements, questions or exclama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…These studies, however, did not explore whether access to contextual information was responsible for the differences observed. Studies that have examined the role of access to contextual information have yielded consistent results both in perception (Grabe et al 2003;Radu et al 2018;Patience et al 2020) and perception-production (Ortega-Llebaria and Colantoni 2014). Grabe et al's (2003) pioneering study showed that three groups of English, Mandarin and Peninsular Spanish speakers did not differ in their discrimination of falling and rising contours in non-speech stimuli (i.e., frequency modulated sine-waves), but differed in their perception of falling contours when they listened to the utterance Melanie Maloney (whose final syllable was manipulated to generate 11 different stimuli with rising and falling contours) produced by a Scottish English speaker.…”
Section: Role Of Task Type In Modulating CLI In Contact Situationsmentioning
confidence: 86%
See 4 more Smart Citations
“…These studies, however, did not explore whether access to contextual information was responsible for the differences observed. Studies that have examined the role of access to contextual information have yielded consistent results both in perception (Grabe et al 2003;Radu et al 2018;Patience et al 2020) and perception-production (Ortega-Llebaria and Colantoni 2014). Grabe et al's (2003) pioneering study showed that three groups of English, Mandarin and Peninsular Spanish speakers did not differ in their discrimination of falling and rising contours in non-speech stimuli (i.e., frequency modulated sine-waves), but differed in their perception of falling contours when they listened to the utterance Melanie Maloney (whose final syllable was manipulated to generate 11 different stimuli with rising and falling contours) produced by a Scottish English speaker.…”
Section: Role Of Task Type In Modulating CLI In Contact Situationsmentioning
confidence: 86%
“…Closer to our study are investigations that have analyzed the role of CLI in the perception of sentence types in early and late bilinguals. These studies have used a variety of methodologies, such as gating paradigms (Marasco 2020), identification tasks (Radu et al 2018;Patience et al 2020) or imitation of resynthesized stimuli (Zárate-Sández 2015) and have yielded mixed results. L1 English-L2 Spanish speakers were the focus of two studies (Zárate-Sández 2015; Marasco 2020).…”
Section: Cross-linguistic Influence and Sentence Typesmentioning
confidence: 99%
See 3 more Smart Citations